Minimum Wage with Optimal Income Taxation - Tomer Blumkin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2004)
Minimum wage legislation is a standard policy tool in most countries. However, the overall merits of minimum wage are controversial due to its potential adverse effects on unemployment. In this paper we construct a simple model in which minimum wage plays an important re-distributive role, alongside income taxation, without generating adverse effects on unemployment.
Keywords: D60; H20; 330